1988
DOI: 10.1182/blood.v71.3.539.539
|View full text |Cite
|
Sign up to set email alerts
|

Blood coagulation factors V and VIII: structural and functional similarities and their relationship to hemorrhagic and thrombotic disorders

Abstract: N ORMAL hemostasis in humans requires the interaction of a large number of plasma glycoproteins with blood platelets and vascular endothelial cells. This interaction results in the generation of a platelet plug and fibrin clot at the site of a vascular injury. Many of the plasma glycoproteins involved in blood coagulation are zymogens to enzymes From the Department of Biochemistry. University of Washington, Seattle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
170
0
2

Year Published

1996
1996
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 402 publications
(174 citation statements)
references
References 49 publications
1
170
0
2
Order By: Relevance
“…Like non‐missense mutations, missense alterations are often reported to induce a severe phenotype, mainly if they modify protein locations that are conserved: (1) in the FVIII of different species (Kane et al , 1988; Pratt et al , 1999); (2) in proteins that present an analogous structure, such as human Cp (Koschinsky et al , 1986), FV (Jenny et al , 1987; Yang et al , 1998), He and Ha. The novel missense mutations that we found (Table II, Fig 2), were located in both the heavy (A1–A2 domains) and the light chains (A3–C1–C2 domains), and they affected residues that were conserved at least in the FVIII protein of all the examined species.…”
Section: Missense Mutationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Like non‐missense mutations, missense alterations are often reported to induce a severe phenotype, mainly if they modify protein locations that are conserved: (1) in the FVIII of different species (Kane et al , 1988; Pratt et al , 1999); (2) in proteins that present an analogous structure, such as human Cp (Koschinsky et al , 1986), FV (Jenny et al , 1987; Yang et al , 1998), He and Ha. The novel missense mutations that we found (Table II, Fig 2), were located in both the heavy (A1–A2 domains) and the light chains (A3–C1–C2 domains), and they affected residues that were conserved at least in the FVIII protein of all the examined species.…”
Section: Missense Mutationsmentioning
confidence: 99%
“…The native protein is a multidomain protein containing three A‐type domains, one B domain and two C‐type domains. The A domains, each sharing ∼ 30% sequence identity among themselves, are homologous to the triplicate A domains present in human ceruloplasmin (hCp) and factor V (FV) (Church et al , 1984; Kane & Davie, 1988). By investigating (http://usexpasy.org) the overall percentage of homology with several other proteins (data not shown), we found that human, rat and murine hephaestin (He) (Vulpe et al , 1999; Frazer et al , 2001; Syed et al , 2002) and murine haphaestin (Ha) (NCBI, protein XP_146812) share a similar percentage of identity with the human FVIII A domains.…”
mentioning
confidence: 99%
“…Factor VIII (FVIII) is a large plasma glycoprotein of 2332 amino acid residues organized in six domains: A1–A2–B–A3–C1–C2 . The three A (3A) domains are homologous to each other, to the A domains of Factor V (FV), and the copper‐binding protein ceruloplasmin .…”
Section: Introductionmentioning
confidence: 99%
“…The relative contribution of plasma and platelet factor V to hemostasis in humans is uncertain, although platelet factor V can support hemostasis in individuals with plasma factor V deficiency (1,4,(6)(7)(8). Factor V is encoded by a single copy gene (1,9) and compared to plasma factor V, human platelet factor V has a more heterogeneous reduced size (due to partial activation and proteolysis within the B-domain) and it is also more resistant to Thromb Haemost 2004; 92: 1349-57 iable size and included forms larger than factor V dimers, the data suggested disulfide-linkage with another platelet protein, possibly multimerin. Immunoprecipitation experiments confirmed that unusually large factor V was associated with multimerin and it remained associated in 0.5 M salt.…”
Section: Introductionmentioning
confidence: 99%
“…
IntroductionFactor V is an important coagulation cofactor that accelerates the conversion of prothrombin to thrombin after conversion to factor Va (1, 2). In humans and animals, congenital factor V deficiency results in bleeding and a partial to complete loss of the factor V that circulates in plasma and in platelets (1, 3-5).The relative contribution of plasma and platelet factor V to hemostasis in humans is uncertain, although platelet factor V can support hemostasis in individuals with plasma factor V deficiency (1,4,(6)(7)(8). Factor V is encoded by a single copy gene (1,9) and compared to plasma factor V, human platelet factor V has a more heterogeneous reduced size (due to partial activation and proteolysis within the B-domain) and it is also more resistant to Thromb Haemost 2004; 92: 1349-57 iable size and included forms larger than factor V dimers, the data suggested disulfide-linkage with another platelet protein, possibly multimerin.
…”
mentioning
confidence: 99%